La place des saints. Virtuosité religieuse et structure du champ religieux - Jean-Pierre Albert (Conserveries Mémorielles)
This papers aims at defining the status and the role of the Christian saints, by analyzing their religious attitude, “the attitude of the virtuosity”, and by situating these personages within a larger religious “field”, in P Bourdieu’s acceptance of the term. The identification of the specificity of the saints is carried out mobilizing three theoretical frameworks (theories of M. Weber, V. Turner and P. Boyer) which complementarity suggests that all three authors focus on the same reality. Then, the question is asked as for whether other religious systems can produce analogous structural effects and, consequently, similar types of religious characters.